Changing Scenario of Groundnut Stem and Collar Rot Diseases in Major Groundnut Growing Areas of Telangana - Chandrakala, J.; Pushpavathi, B.; Sudini, Harikishan; Triveni, S.; Supriya, K. (International Journal of Economic Plants, 2024)
A roving survey was carried out in major groundnut-growing regions of Telangana state during kharif 2020 and kharif 2021 season aimed to assess the incidence of stem rot (Sclerotium rolfsii) and collar rot (Aspergillus niger) disease. The study revealed varying disease incidences at different stages and locations. The highest per cent disease incidence of stem rot from vegetative stage (22.05%) was recorded in Kalvapalle village of Mahabubabad district while maximum collar rot incidence (10.57%) was recorded in Choppadandi village of Karimnagar district. Lowest stem rot (7.81%) and collar rot (3.27%) incidence was recorded in Varkal village of Nalgonda district and Chakalpalle village of Wanaparthy district. Conversely at harvest stage maximum stem rot incidence (9.04%) was observed in Venkatapur village of Warangal district and maximum collar rot incidence (4.31%) was observed in Gundyala village of Mahabubnagar district. Lowest stem rot incidence (1.41%) was recorded in Gurthur village of Mahabubabad district while Collar rot incidence (1.69%) was recorded in Kondapur village of Nalgonda district.